Paleontology in Argentina: history, heritage, funding, and education from a southern perspective - Fernández, Diana Elizabeth (2014)
“(...) y siendo estos monumentos un testimonio auténtico y demostrable de que en la antigüedad hubo en esta región americana, sea antes o pos el diluvio, racionales gigantes (…)” …and these monuments are an authentic and demonstrable testimony that in antiquity there was in the American region, either before or after the Flood, giant rational beings... Translated from a letter by Esteban Álvarez del Fierro to the then Buenos Aires mayor, about his discoveries in Arrecifes (Gutiérrez, 1866).